eBusiness maturity and regional development - Paul Beynon-Davies (International Journal of Business Science & Applied Management (IJBSAM), 2007)
This paper describes the experience of a major research centre supporting knowledge transfer in the area of eCommerce to SMEs. It debates with issues surrounding the integration of academic research with practical support to the SME community. For this purpose the use of an eBusiness framework as a platform for eBusiness maturity assessment is proposed. These devices are seen as key to the work of research centres such as ours in addressing the future challenges for smeeBusiness.
Keywords: 650; ebusiness; maturity assessment; regional development